Peran BMT Dalam Upaya Pemberdayaan UMKM: Ditinjau Dari Perspektif Ekonomi Syariah - Banibas, Risma; Sudirman, Andi; Fauziah, Fauziah (Sekolah Tinggi Ilmu Ekonomi (STIE) Tri Dharma Nusantara Makassar, 2024)
Baitul Mal wa al-Tamwil (BMT) is a legal entity financial institution that carries out its operations in accordance with sharia principles. Apart from operating in the financing sector, BMT also operates in the savings and investment sector with a profit sharing pattern. BMT generally adheres to the principles of faith and devotion to Allah SWT. This is clear because BMT is a cooperative based on Islamic teachings. The function of this institution is to support the improvement of the economic efforts of micro and small entrepreneurs based on the sharia system. Therefore, BMT is used by its members as a household tool to overcome the problem of lack of liquidity or lack of capital independently. So this reciprocal relationship creates benefits for its members, especially for micro, small and medium enterprises